Odpowiedzi

2010-03-11T14:51:35+01:00
P=26cm²
a=3cm
h=4cm
b=?

P=½*(a+b)*h
26=½*(3+b)*4/2
52=(3+b)*4//4
13=3+b
b=13-3
b=10[cm]

Długośc drugiej podstawy wynosi 10cm
Proszę o naj:)
1 5 1
2010-03-11T14:53:32+01:00
P=1/2*(a+b)*h podstawiamy do wzoru

P=26cm a=3cm h=4cm
26=1/2*(3+b)*4
26=(3+b)*2

b=26/2-3
b=13-3
b=10

prosze o naj
2 5 2
Najlepsza Odpowiedź!
2010-03-11T14:58:47+01:00
A=3 cm
h=4 cm
b=?
P=26 cm^2

P=(a+b)/2*h
26=(3+b)/2*4
26=(3+b)*2
3+b=13
b=13-3
b=10 cm

Spr.
P=(10+3)/2*4
P=13*2
P=26 cm^2
Odp.
Długośc drugiej podstawy wynosi 10 cm.
pozdrawiam:)